Effect of Various Infusion Solutions on Microrheology - V. V. Moroz; L. V. Gerasimov; A. A. Isakova; Yu. V. Marchenkov; E.P. Rodionov (Общая реаниматология, 2010)
Objective: to evaluate the in vitro and in vivo effects of various infusion solutions on red blood cell rheology in the early posttraumatic period. Material and methods. The in vitro study assessed crystalloids, albumin, dextrans, modified gelatin, and different generations of hydroxyethyl starches (HES). The preparations were added to blood in a 1:10 dilution; before and after their addition, the values of erythrocyte aggregation and erythrocyte deformability were estimated. The in vivo study covered 59 patients with severe concomitant injury, who were divided into 3 groups: 1) those who received crystalloids only; 2) those who had crystalloids + 6% HES 130/0.42; 3) those who had crystalloids + gelofusine. The same parameters of red blood cell rheology were estimated as in the in vitro study. Results. Albumin, repolyglycan, and HES 130/0.42 were found to have the most pronounced disaggregatory effect in vitro. At the same time, polyglycan, gelofusine, and HES 450/0.7 in particular, enhanced erythrocyte aggregation. In vitro, albumin, HES 130/0.42, and HES 200/0.5 exerted the most beneficial effect on erythrocyte deformability whereas dextrans made the latter worse and HES 450/0.7 and gelofusine failed to have a considerable effect on it. The early posttraumatic period was marked by progressive erythrocyte hyperaggregation and phasic deformability changes. Significant microrheological disorders persisted in the patients on infusion therapy with crystalloid solutions only. Addition of HES 130/0.42 to infusion therapy improved the deformability of erythrocytes and lowered their aggregation. The use of gelofusine as a component of infusion therapy caused a moderate increase in erythrocyte aggregation. Key words: infusion therapy, erythrocyte deformability, erythrocyte aggregation.